Evaluating mental stress test in coronary artery disease treadmill positive patients (Medical Journal of Indonesia, 2002)
Evaluation of CAD is more routinely done by treadmill test (TMT i.e. physical strain) than the more frequently occurring mental strain, so a study was planned to assess the provocability of ischaemia by various mental tasks in patient with positive TMT. Thirty educated subjects, positive on TMT were put on a 24 hour holter monitoring. During this time, subjects were assessed by Mental Stress Test (MST) by subjecting to various mental tasks - (a) Time stress test (b) Mental arithmetic test (c) Reading test (d) Zeigarnik effect test and observed for heart rate, blood pressure and ischaemic/arrhythmia responses. The results showed that the male : female ratio was 14:1 with a mean age of 57 ± 8.03 years. The mean change produced during MST in (a) heart rate was 9.16 (SD ± 1.24)/min (b) SBP was 8.86 (SD ± 1.32) mmHg (c) rate pressure product was 82x103; which were statistically low (p<0.001) when compared to haemodynamic changes with TMT. Ischaemia was inducible in only one subject by MST and no increased incidence of arrhythmias during MST was noticed. The low yield of inducible ischaemia by MST when compared to TMT could be due to poor haemodynamic responses achieved by MST when compared to responses of TMT (p<0.001). It is concluded that mental stress does produce ischaemic changes. More intense and sustained MST's which could bring about significant haemodynamic changes are required for inducing ischaemia as by TMT. (Med J Indones 2002; 11: 36-40) Keywords: coronary, ischaemia, mental task, stress test, treadmill